The subject and the participant of corporate legal relations: features of their legal understanding and interpretation - Kolosov, Ruslan (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The necessity in clarifying the conceptual and terminological bases of corporate legislation arose with the emergence and development of corporate law. One of the directions of this is the study of terms «subject of corporate relations» and «participant in corporate relations», the identification of their common features and differences, which should contribute to the improvement of existing legislation in this area.